Creating Flight Safety Risk Analysis System: Samsun Çarşamba Airport Example - Uzun, Omer Faruk; Hosbas, Ramazan Gursel (TURKISH CHAMBER CIVIL ENGINEERS, 2026)
This study examines the risk analysis and results carried out around Samsun & Ccedil;ar & scedil;amba Airport through the Flight Safety Risk Analysis System (FSRAS), which was developed to increase aviation safety and minimize risks. It focuses on the effects of land management and zoning legislation on flight safety associated with development around the airport. In the study, possible threats to flight safety due to environmental factors and human activities were determined and risky areas were analysed. With the software developed using the Python programming language, dynamic spatial queries were made via Google Maps and Google Places APIs, and the results were visualized on the QGIS platform. The analysis revealed the existence of structures that could threaten flight safety, such as a waste separation facility within the 13-kilometer risky area, fuel stations in the 15-kilometer risky area, places of worship and schools in the 3-kilometer risky area. In this context, it is recommended to minimize risky construction around the airport and to implement land management policies in accordance with international standards.
Keywords: Flight safety; risk analysis; transport safety; land management; disaster management; Engineering